UPAYA PERLINDUNGAN HUKUM TERHADAP PEMEGANG SAHAM MINORITAS DALAM MELINDUNGI KEPENTINGANNYA - Dian Indra Prabawati Dharma, Kadek; Artadi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013)
This paper shall be entitled as "Legal Protection For Minority Shareholders to protect their interest". By using the normative research method this paper shall examine on how to provide legal protection for minority shareholders whose interests in are set aside by the majority shareholders to minority shareholders felt abandoned and often harmed by the company. In the capital market, trust is an essential factor. It varies from Public confidence in the value of shares, true statements, prospect of future profits, government policies in support of the capital markets, through the process of legal certainty in case of violation. In response, legislation was made so that minority shareholders possess legal protection.
Keywords: Minority shares, legal protection, the Capital Market